2017
DOI: 10.1038/emm.2017.191
|View full text |Cite
|
Sign up to set email alerts
|

Trib2 regulates the pluripotency of embryonic stem cells and enhances reprogramming efficiency

Abstract: Embryonic stem (ES) cells are pluripotent cells characterized by self-renewability and differentiation potential. Induced pluripotent stem (iPS) cells are ES cell-equivalent cells derived from somatic cells by the introduction of core reprogramming factors. ES and iPS cells are important sources for understanding basic biology and for generating therapeutic cells for clinical applications. Tribbles homolog 2 (Trib2) functions as a scaffold in signaling pathways. However, the relevance of Trib2 to the pluripote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…These data indicated that the promotive action of XIST to LSCC progression exerted through directly bating miR-125b-5p expression. Tribbles homolog 2 (TRIB2) belongs to Tribbles pseudokinases, playing a pivotal role in etiology of multifarious cancers [26,27]. Investigators found TRIB2 expression was elevated in colorectal cancer (CRC) and TRIB2 overexpression promoted cell proliferation and deferred cellular senescence of CRC partially relying on direct regulation of p21 expression and transcription factor AP4 expression [28].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that the promotive action of XIST to LSCC progression exerted through directly bating miR-125b-5p expression. Tribbles homolog 2 (TRIB2) belongs to Tribbles pseudokinases, playing a pivotal role in etiology of multifarious cancers [26,27]. Investigators found TRIB2 expression was elevated in colorectal cancer (CRC) and TRIB2 overexpression promoted cell proliferation and deferred cellular senescence of CRC partially relying on direct regulation of p21 expression and transcription factor AP4 expression [28].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the tribble family, tribbles homolog 2 (TRIB2) is a mitosis blocker that regulates embryo and germ cell development [18]. It has been reported that, as a scaffold protein [19], TRIB2 plays a critical role in various biological processes as well as in pathological conditions, especially in tumor development [20,21]. For instance, the overexpression of TRIB2 may accelerate the acute myeloid leukemia (AML) through activating C/EBPα pathway [22]; in liver cancer, TRIB2 promoted cell proliferation and transformation via improving the stabilization of YAP through the E3 ubiquitin ligase βTrCP [23].…”
Section: Discussionmentioning
confidence: 99%
“…It comprises an N-terminal domain, a C-terminal domain, and a central pseudokinase domain that contains a Ser/Thr protein kinase-like domain but lacks ATP affinity and catalytic activity [2]. In the absence of kinase activity, TRIB2 functions as a scaffold protein to regulate different signaling pathway in fundamental biological processes as well as in pathological conditions, including cancer [3]. TRIB2 plays a crucial role in regulating various cellular processes in cancer, such as proliferation, apoptosis and drug resistance [4–6].…”
Section: Introductionmentioning
confidence: 99%